Proper Acknowledgment? - East, J. (Journal of University Teaching and Learning Practice, 2005)
The concern in Australian universities about theprevalence of plagiarism has led to the development ofpolicies about academic integrity and in turn focusedattention on the need to inform students about how toavoid plagiarism and how to properly acknowledge.Teaching students how to avoid plagiarism can appear tobe straightforward if based on the notion that plagiarism iscopying without proper acknowledgment. This paperreviews the term ‘proper acknowledgment’ in theacademic context and argues that properacknowledgement can be a matter of context andperception. In this paper forms of plagiarism arereviewed, reasons for student plagiarism are consideredand different contexts for acknowledgement and howthese fit in with concepts of attribution and originality arediscussed. Comments from international students new toAustralian academic culture provide insights and revealthat students in trying to master the rules ofacknowledgment can be perplexed and concerned aboutwhen and why they should acknowledge.